New opportunities for identifying the risk of cardiovascular events in young people: the role of familial hypercholesterolemia - V. S. Emelyanchik; S. Yu. Nikulina; E. Yu. Emelyanchik; A. V. Protopopov (Российский кардиологический журнал)
A search was made for publications on modern methods for determining cardiovascular risk in young people with positive family history for early cardiovascular events. The use of various screening options allows timely identification of patients with heterozygous familial hypercholesterolemia who have a high cardiovascular risk. The most effective method is cascade screening. Cardiovascular risk assessment systems that include a family history of early cardiovascular events and lipid profiles in individuals under 40 years of age provide prevention of atherosclerosis. In the diagnosis of risk, the lipoprotein (a) is of particular clinical importance, elevated concentrations of which are associated with a high risk of vascular damage and an unfavorable course of atherosclerosis.